Linguistics and anthropological research field A study in the impact of the linguistic approach in the interpretation of social and cultural realities - kaouache, aziz (Journal of Social Sciences and Humanities, 2021)
Linguistic anthropology is one of the most important intercultural fields of knowledge at the moment. It examines the interrelationship between language and various human social activities and practices, ie the influence of language and its role in the formation of society and culture, as well as the impact of social practices in language. Social. It is a branch of anthropology. If linguistics deal with language independent of its social human context, ie, it is concerned only with structural, grammatical and semantic aspects, linguistic anthropology goes beyond this to address language in its living form, ie in the context of cultural practices and various human activities. Through its anthropological approach, linguistic anthropology demonstrates how language represents communication, constitutes social identity and participation in a group, organizes cultural beliefs and ideologies widely and develops cultural representation of the natural and social world. In this article we also address some of the important issues discussed in this science, such as the relationship between language and culture, and what are called linguistic communities, and focus on the idea of "linguistic society," a society that uses a single language of different dialects, and all these issues and others contained in this research are An answer to the problem of this study.